Detecting emotions and depression through voice - Gunawan, Teddy Surya (2021)
A deep learning algorithm can detect emotion, including depression, using a voice signal. The system, developed by Teddy Surya Gunawan at the International Islamic University Malaysia, could be used by suicide prevention call centres and psychological counsellors.